The Philosophy of Progressivism in Education Based on The Merdeka Curriculum - Dudi Kiswanto; Syuhadak, Syuhadak; Agil, Idrus Muchsin Bin (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The curriculum serves as the core of education, guiding and encompassing all learning activities to achieve educational objectives. As time and technology progress, the curriculum must evolve to ensure that the education provided to students remains relevant to their future needs. In Indonesia, curriculum development has now progressed to the implementation phase of the Merdeka Curriculum, an initiative designed to keep pace with the dynamic nature of modern advancements. This study aims to explore the concept of the Merdeka Curriculum from a progressive philosophy perspective. The research is qualitative in nature and uses a literature review approach. Data were gathered through observations, interviews, and documentation, and were analyzed using the Miles and Huberman model. The findings suggest that the Merdeka Curriculum ensures that education addresses not only academic content but also the development of character and essential life skills, aligning with the progressive philosophy that views education as a continuous and evolving process.